THE EFFECT OF SOME TREATMENTS ON MICROBIOLOGICAL CONTENT OF - Narin M.Amin (Mesopotamia Journal of Agriculture)
Total bacterial counts slightly decreased during 35 days storage while coliform bacteria , yeasts and molds significantly reduced . Psychrophilic bacteria and brucella however, started to decrease on the second week of storage . Generally , refrigeration had a slight effect on microbial contents of both cheeses . Freezing had significantly reduced microbial content in both cheese . There was a reversibil relationship between freezing period and microbial contents. Freezing caused a reduction of total bacteria count, psychrophilic bacteria,coliform bacteria,yeasts and molds as these microorganisms disappeared from the first week of storage . Freezing also caused a significant reduction in brucella content.A gradual decrease in total bacterial counts and coliform bacteria were observed upon thermal treatment , but yeasts , molds and psychrophilic bacteria were destroyed at 70ºCfor 5 days in local cheese samples .Cheese made from pasteurized milk did not contain brucella as compared to local cheese.Pickling of local cheese samples in salt solution at concentration of 3,5and 10% resulted in a significant decrease of total bacterial counts .There was a reversibil relationship between pickling and microbial contents .